Relasi Orang Tua dan Anak; Kajian Tematik Term Quranik Gulām dalam Tafsir Al-Kabīr - Asrul (Studia Quranika, 2021)
This study focuses on analyzing the term of gulam and its derivation in the Qur’an. This is crucial term due to there are many definition used by the Qur’an that explaining about children. The purpose of this study was to find al-Qur’an cues about the relationship between parents and children. The research method employs library research by constructing Tafsir Al-Kabīr by Fakhruddin Al-Razi as the object of study. Starting with tracing all the terms of gulām in the Qur’an as a seminal concept, conducting language studies, determining the theme of the verse, mapping out the interpretations, and reviewing the result of studies, then formulating new concepts related to the issues being raised. This study reveals five formulations of parent-child relations : philosophical relations, theological relations, social relations, economic relations, and protection relations. The five relations are to describe the ideal relationship between parents and children in addition. It also generatesessential contributions to observers and authorities regarding children, such as the religious, educational, social, economic, legal, and child protection aspects.